"Our Work Has to Go Way Beyond the Classroom Doors" - Terri Suico (University of Oklahoma Libraries, 2020)
Terri Suico facilitates a conversation between Sarah Park Dahlen and Gabrielle Atwood Halko, who co-edit a bi-annual journal, Research on Diversity in Youth Literature.